A study on ovary autotransplantations without vascular pedicle in rats. - Timurkan, H; Risvanli, A; Akpolat, N; Gulacti, I; Ulakoglu, E (Elsevier Science Inc, 2005)
[Abstract Not Available]
Conjoint Annual Meeting of the American-Society-for-Reproductive-Medicine/Canadian-Fertility-and-Andrology-Society -- OCT 15-19, 2005 -- Montreal, CANADA